Master of Faculty Resource Science and Technology - Universiti Malaysia Sarawak, Faculty of Resource Science and Technology (Universiti Malaysia Sarawak (UNIMAS), 2020)
Faculty Resource Science and Technology Bachelor's Degree Certificate yr 2020 for 471 Students